Вплив абіотичних факторів на початок нересту у Carassius gibelio в умовах Дніпровсько-Орільского заповідника - Губанова, Надія Леонідівна; Gubanova, Nadiia; Hubanova, Nadiia; Gubanova, N.; Gubanova, N. L.; Gubanova, Nadezhda; Hubanova, N. L.; Hubanova, N.; Горчанок, Анна Володимирівна; Horchanok, Anna; Horchanok, A.; Horchanok, A. V.; et al. (Дніпровський ДАЕУ, 2019)
Метою даної роботи було встановити значення чинників, що впливають на процес нересту у карася сріблястого (Carassius gibelio) як найбільш розповсюдженого виду у водоймах заповідника. Influence of abiotic factors on the beginning of spawning in prussian carp Carassius gibelio. Rapid warming in the spring, combined with more normal rainfall, can stimulate earlier spawning. The duration of spawning depends largely on the time of its occurrence: the sooner the spawning begins, the longer the spawning period. Climatic features during the spawning season are mostly corrected during its closure. Water temperature at the beginning of spawning depends on climatic conditions.
Influence of abiotic factors on the beginning of spiritual at Carassius gibelio in the conditions of the Dneprovsko-Orils reserve
Губанова Надія Леонідівна https://orcid.org/0000-0003-0617-2498 Горчанок Анна Володимирівна https://orcid.org/0000-0003-0103-1477
Keywords: Carassius gibelio; Carassius gibelio; нерест; nerest; розмноження риб; rozmnozhennia ryb